Rancang Bangun Game Edukasi untuk Membantu Proses Pembelajaran Matematika Kelas 3 SD dengan Menggunakan Unity - Suwarno .; Vincent Eng (Universitas Internasional Batam, 2021)
Technology development has been rapidly growing, which has been affecting on traditional education system. Starting on March 2020, government decided to assign all education system to be done in online in order to prevent the spread of covid-19 virus. As an attempt to enforce this online learning system, author builds an education game that grant students to improve their knowledge in primary grade mathematics. Through this game, students will be encountering a set of arithmetic operations in mathematics up to 3rd grade level. This game will be build in Unity and C# programming language by using SDLC Waterfall method.